Myeloid Sarcoma Type of Acute Promyelocytic Leukemia With a Cryptic Insertion of RARA Into FIP1L1: The Clinical Utility of NGS and Bioinformatic Analyses - Wang, Yongren; Rui, Yaoyao; Shen, Ying; Li, Jian; Liu, Poning; Lu, Qin; Fang, Yongjun (Frontiers in Oncology, 2021)
Background: Acute promyelocytic leukemia (APL) is characterized by a reciprocal translocation t(15;17)(q22;21), however, several other complex variant translocations have also been reported. The FIP1L1-RARA fusion gene has recently been reported as a novel RARA-associated fusion gene. Objectives: We report a case of de novo myeloid sarcoma (MS) type of APL with FIP1L1-RARA found by next-generation sequencing (NGS) that was not detected by conventional analysis for RARA-associated translocations. Methods: To investigate the underlying pathogenesis of a unique case, we performed typical morphological, magnetic resonance imaging (MRI), conventional tests for PML-RARA dual-fusion translocation probe, high-through sequencing, and NGS. Meanwhile, bioinformatic analyses were done by using public repositories, including ONCOMINE, COSMIC, and GeneMANIA analysis. Results: A 28-months-old girl with a complex karyotype that includes 46,XX,t(4;17)(q12;q22)[9]/46,idem,del(16)(q22)[3]/45,idem,-x,-4,-9,-15,del(16)(q22),+marl,+mar2,+mar3[7]/46,xx[3], c.38G>A (p.Gly13Asp) in the KRAS gene, and a cryptic insertion of RARA gene into the FIP1L1 gene was diagnosed with APL complicated by the de novo MS. Conclusion: we report a FIP1L1-RARA fusion in a child with APL who presented with an extramedullary tumor in the skull without the classic karyotype using NGS, whom we treated with good results. NGS analysis should be considered for APL variant cases. Further experimental studies to the association between the mutation in the KRAS gene and FIP1L1-RARA fusion on the clinical phenotype and progression of APL are needed to identify more effective therapeutic targets for APL.